Volumetric properties of carbon dioxide + acrylic acid binary in the context of supercritical precipitation polymerization - Menossi, Matías; Milanesio, Juan M.; Camy, Séverine; Harrisson, Simon; Strumia, Miriam; Destarac, Mathias (The Journal of supercritical fluids, 2020)
[Display omitted] •Phase transitions and pseudo-continuous density vs pressure experimental data was obtained for ‘carbon dioxide + acrylic acid’ binary systems.•The phase boundaries were fitted using the RKPR cubic equation of state.•Excess volumes at high pressure were derived from density data and they show highly negative behavior. Acrylic acid can be polymerized by precipitation in different solvents. Carbon dioxide is an interesting solvent given its tunable density and solvent power depending on the pressure and temperature. These physicochemical characteristics make it possible to solubilize some polar compounds in CO 2 depending on temperature and pressure. In this work, we report pressure vs volume pseudo-continuous curves at constant temperature for the CO 2 + AA binary mixture. They were determined in a fully computerized variable-volume high-pressure view cell capable of monitoring the position of the piston. The experimental data is simultaneously isoplethic and isothermal and it covers a wide range of pressures (up to 20 MPa). Using this raw experimental data, other properties were determined such as liquid-vapor phase boundaries, density and excess volumes. The temperature range was 313.15–363.15 K and the mole fraction of AA in the mixture was increased from 0.044 to 0.594.